Manohar Malgonkar as a Feminist - Jaiswal, Anil Kumar; Shanker, Rama (International Journal of Membrane Science and Technology, 2023)
This research paper illustrates the concept of female characters in the novels of Manohar Malgonkar. Branded as an entertainer and story teller, the deeper qualities of his fiction have been neglected or unperceived by many. The various articles by commentators do not seem to bring out the merits of the author as a significant Indo-English novelist. The few researchers who have taken up his novels seem to have failed to highlight his exceptional command over the English language. A casual reading of his novels may make the reader fall in line with the biased comments made by earlier critics. It is also intended to bring out a balanced view of the greatness of the author. Succumbing to this temptation also, this attempt to study the concept of women versus tradition in Malgonkar’s novels is made here. In this study I have taken up his five full-fledged and mature novels to explain Malgonkar as a feminist - Distant Drum, Combat of Shadows, The Princess, A Bend in the Ganges, and The Devil’s Wind. Key words: Traditions, Inferiority complex, Anglo-Indian, Orthodox, Reminiscence, Relationship, and Domination, Feminism etc.